Effects of economic growth, foreign direct investment and internet use on child health outcomes: empirical evidence from South Africa. Issue 1 (1st January 2020) - Salahuddin, Mohammad; Vink, Nick; Ralph, Nicholas; Gow, Jeff
ABSTRACT: This study examines the effects of economic growth and foreign direct investment (FDI) on child health outcomes measured by Infant Mortality Rate (IMR) and Child Mortality Rate Under 5 (CMRU5) with several control variables such as corruption, inequality and HIV among others. It analyzes South Africa's annual time series data for the period 1985–2016. As variables were found with mixed order of integration, Autoregressive Distributed Lag (ARDL) model is applied to determine cointegration and estimate short-run and long-run coefficients. Results indicate that economic growth and FDI have negative significant effects on both indicators of child health outcomes in both the short run and the long run. This implies that both economic growth and FDI contribute towards reducing IMR and CMRU5 in South Africa and thus help improve child health outcomes. Toda and Yamamoto (TY) causality test confirms causal association between these variables. Policy implications are discussed.